Acceleration of Ozone Decomposition and ·OH Generation by Hydroxylamine. (3rd March 2016) - Zhang, Jing; Zhang, Yong-Li; Shi, Ya-Nan; Lin, Jie; Zhou, Peng; Zhang, Wan-Qing; Xu, Jian-Wei
ABSTRACT: Most of protonated amines show very low reactivity with ozone in the process of generating hydroxyl radical (·OH). This study proved that protonated hydroxylamine (HA) can accelerate the decomposition of ozone and promote the yield of ·OH. Benzoic acid (BA) was used as ·OH probe, the stimulation of ozone decomposition and ·OH generation by HA in the condition of pHs ranging from 3.0 to 8.0 were studied. The results revealed the effect of HA, especially the protonated form of HA, on the ozone decomposition. Moreover, two reaction pathways of the reactive oxidant formation in O3 /HA process were proposed: (1) protonated HA reacted with ozone by the way of direct electron transfer to produce O3 ·- ; (2) unprotonated HA reacted directly with ozone to form O2 ·- and O2 ·- later reacted with O3 to form O3 ·- .